2014
DOI: 10.4041/kjod.2014.44.2.96
|View full text |Cite
|
Sign up to set email alerts
|

The role of polymorphisms associated with early tooth eruption in dental and occlusal traits in East Asian populations

Abstract: ObjectiveA recent study suggested that rs6504340, a polymorphism within the homeobox B (HOXB) gene cluster, is associated with the susceptibility for malocclusions in Europeans. The resulting malocclusions require orthodontic treatment. The aim of this study was to investigate the association of rs6504340 and other dentition-implicated polymorphisms with dental and occlusal traits in Korean and Japanese populations.MethodsThe study participants included 223 unrelated Koreans from the Busan area and 256 unrelat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
1
0
1
Order By: Relevance
“…The SNP rs8079702, in proximity to potassium channel gene KCNJ2, exhibited decreased longitudinal QTc variance (Mints, Zipunnikov, Khurram, Calkins, & Nazarian, 2014). Besides, it has been shown that associated with the timing of first tooth eruption and the number of teeth at one year of age were genotyped in Japanese and Korean populations (Yamaguchi et al, 2014). The mutation at rs8079702 may affect the binding of KCNJ2 gene to CEBPB protein by the Bioinformatics prediction (http://pubs.broad insti tute.org/mamma ls/haplo reg/ haplo reg.php) (Ward & Kellis, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The SNP rs8079702, in proximity to potassium channel gene KCNJ2, exhibited decreased longitudinal QTc variance (Mints, Zipunnikov, Khurram, Calkins, & Nazarian, 2014). Besides, it has been shown that associated with the timing of first tooth eruption and the number of teeth at one year of age were genotyped in Japanese and Korean populations (Yamaguchi et al, 2014). The mutation at rs8079702 may affect the binding of KCNJ2 gene to CEBPB protein by the Bioinformatics prediction (http://pubs.broad insti tute.org/mamma ls/haplo reg/ haplo reg.php) (Ward & Kellis, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Estudios recientes proporcionan evidencia de la asociación entre los genes EDA y XEDAR y el apiñamiento dental 34 . Diversos estudios han proporcionado evidencia de las asociaciones entre los factores genéticos y los rasgos dentales comunes, como el tamaño de los dientes 35,36 .…”
Section: Síndromes Asociados a La Agenesiaunclassified